Mandarin virtual winter camp 2022 – two worlds connected online - Wan Jumani, Fauzi; Kang, Mei Feng (2022)
6 March 2022 – Universiti Malaysia Pahang through its Centre for Modern Languages (CML) and Centre for International Relations (CIR) successfully organized a two-day virtual winter camp in collaboration with Tianjin Normal University (TNU), which was held from 5 to 6 March 2022 via Voov. The camp was joined by 31 students from Universiti Malaysia Pahang who are currently doing their dual degree programme. These students need to pass their Hanyu Shuiping Kaoshi (HSK) level 3 in order for them to pursue their studies in China.